Политическая деятельность хана Младшего жуза Ералы ( 1791-1794 гг.) - Janguzhiyev, M. S.; Zhapekova, G. К.; Balzhanova, G. Z. (Journal of history, 2023)
The article consider the socio-political activity of Yeraly Khan, who occupies a special place among the historical figures of the Kazakh state of the XVIII century. His life is associated with the most difficult period in the history of the country and Yeraly Khan, understanding the vicissitudes of the political climate of that time, tried to make well-adjusted decisions based on his own understanding and support of the policy of his father Khan Abulkhair for the benefit of the state. He served faithfully to his people, showing high activity in the political events of the XVIII century. He was one of the khans, who led the struggle against the liquidation of the khan's power by the Russian administration. In the presented work, the conclusion is made about the decisive role of representatives of the Abulkhair clan in the management of the Younger Zhuz and neighboring adjacent territories. During this period, khans were elected not only in Kazakh society, but also outside the Kazakh state from representatives of the Genghis Khan dynasty, so they are presented in the article as the real owners of the khan's power. The results of the study show the difficulties of the political situation of that time, the need to carry out various vectors of the foreign policy course of the Kazakh state. A systematic analysis of the complex of sources, historical literature and archival documentary data allows a sufficiently deep and comprehensive study of the problem. The reconstruction of an integral historical image shows the outstanding personality of Yeraly, who entered the history of the Kazakh people in the category of great figures of Kazakh history. Keywords: Yeraly Khan, personality in history, Kazakh state, Orenburg Commission, Kazakh-Russian relations.